Systematic generation of a CAPE-OPEN compliant simulation module from GAMS and FORTRAN models - Domancich, Alejandro Omar (2010)
The adaptation of complex existing modules so that they meet the CAPE-OPEN (CO) standard is important in order to take advantage of previous work done for the simulation of processes. In this work we present the design and implementation of two different Operation-Unit (OU) modules that support the CO interface. Each resulting OU satisfies the definitions and guidelines established by the standard. The first module consists of a CO-compatible component for the steady-state simulation of a multi-bed ammonia reactor, whose original code had been written in FORTRAN. The second one, which also supports the CO interface, it is a GAMS-compatible module of a reactive distillation column. In order to develop these modules, an existing CO wizard that targets the mechanical generation of the OU Package was used. This wizard generates a Visual Basic project that contains the OU's source code and its installation package. In particular, the calculation routine and the Graphical-Unit Interface (GUI) were implemented. Before implementing the interfaces, an analysis of requirements for the correct interaction between the OU and the other simulator components was carried out. Both modules embedded in HYSYS take advantage of its complete property-package, which complements GAMS and FORTRAN in order to carry out the accurate computation of the chemical and equilibrium properties. © 2009 The Institution of Chemical Engineers.